Mind the gap: examining policy and social media discourse on Long COVID in children and young people in the UK - Macarena Chepo; Sam Martin; Noémie Déom; Ahmad Firas Khalid; Cecilia Vindrola-Padros (BMC Public Health)
Abstract Background Long COVID in children and young people (CYP) has posed significant challenges for health systems worldwide. Despite its impact on well-being and development, policies addressing the needs of CYP remain underdeveloped. This study examines UK Long COVID policies using ethical frameworks, integrating policy and social media analyses to explore public and professional concerns. Methods A mixed-methods approach was applied. Policy documents were reviewed using Thompson et al.'s pandemic preparedness framework and Campbell and Carnevale’s child-inclusive ethical model. Social media discourse (12,650 posts) was analysed using Brandwatch™ to identify key themes around CYP and Long COVID policies. Data was collected and triangulated through the LISTEN method, which integrates policy analysis with social media discourse to ensure a holistic understanding of systemic gaps and public perceptions. Results Analysis highlighted gaps in accountability, inclusiveness, and transparency in policy development. Social media data reflected significant public dissatisfaction, primarily critiquing government accountability (90% of posts) and delayed policy responsiveness (29% of posts). Key ethical challenges included limited CYP representation and unequal access to services. Conclusions Recommendations include improving transparency, incorporating CYP perspectives in policymaking, and ensuring equitable access to care. These findings provide a foundation for ethically sound and inclusive policies addressing Long COVID in CYP.